Biomarkers of muscle quality: N‐terminal propeptide of type III procollagen and C‐terminal agrin fragment responses to resistance exercise training in older adults. Issue 2 (7th November 2013) - Fragala, Maren S.; Jajtner, Adam R.; Beyer, Kyle S.; Townsend, Jeremy R.; Emerson, Nadia S.; Scanlon, Tyler C.; Oliveira, Leonardo P.; Hoffman, Jay R.; Stout, Jeffrey R.
Abstract : Background: N‐terminal peptide of procollagen type III (P3NP) and C‐terminal agrin fragment (CAF) are circulating biomarkers that are related to lean body mass in older adults. P3NP is a circulating marker reflective of muscular structural remodeling while CAF is a circulating marker of neuromuscular remodeling. As resistance exercise is an established intervention that can effectively improve muscle quality, we sought to evaluate circulating biomarker changes corresponding to a resistance exercise intervention in older adults. Methods: Twenty‐three older adults (aged 61 to 85 years) were randomized into an intervention (6‐week resistance training) or control group. Resting circulating P3NP, CAF, lean body mass (LBM), muscle cross‐sectional area (CSA), muscle strength, and muscle quality were determined at baseline and after the intervention or control period by enzyme‐linked immunosorbent assay, dual‐energy X‐ray absorptiometry, ultrasound, leg extension, and relative strength, respectively. Changes in circulating biomarkers and measures of muscle mass and quality were evaluated with repeated‐measures analysis of variance; clinical interpretations were made with magnitude‐based inferences, and relationships between variables were evaluated with bivariate correlations. Results: The short‐term resistance exercise intervention was effective at improving muscle quality by 28 % ( p  < 0.001) despite no significant changes in lean body mass. Baseline circulating P3NP was somewhat lower in older women (4.15 ± 1.9 ng/mL) compared with older men (4.81 ± 2.1 ng/mL). The exercise intervention tended to increase circulating P3NP (baseline = 4.53 ± 1.80 to post = 4.88 ± 1.86) and was significantly correlated with changes in LBM ( r  = 0.422, p  = 0.045). At baseline, women (3.91 ± 1.12 pg/mL) had somewhat higher circulating CAF than men (3.47 ± 1.37 pg/mL). Circulating CAF increased by 10.4 % (3.59 to 4.00 pg/ml) in older adults following 6 weeks of resistance exercise training. Changes in circulating CAF were significantly related to changes in CSA of the vastus lateralis ( r  = 0.542, p  = 0.008). Conclusions: Assessment of P3NP and CAF from blood samples may provide minimally invasive and clinically informative measures of skeletal muscle status in older adults. Circulating CAF appears to increase in response to short‐term resistance exercise training in older adults to a clinically meaningful magnitude. Changes in circulating P3NP in response to the intervention were less clear but appear to reflect muscle hypertrophy. Further research is needed to elucidate whether P3NP, CAF, or other biomarkers can reflect muscle qualitative adaptations with larger and longer studies.